Identification of P-glycoprotein/multidrug resistance genes from model organisms. - Allikmets, R.; Gerrard, B.; Stewart, C.; White, M.; Dean, M. (Leukemia, 1993)
Using degenerate oligonucleotides from conserved portions of the ATP-binding domain of the active transporter genes, several new members of this gene superfamily have been cloned from Drosophila, Saccharomyces cerevisiae, and E. coli DNA. The Drosophila and E. coli genes contain two sets of transmembrane domains and two ATP-binding domains, whereas the yeast gene contains single transmembrane and ATP-binding domains. All three genes show a high degree of similarity to the mammalian P-glycoprotein/multidrug resistance (MDR) genes. The E. coli sequence is the only known transporter gene containing both ATP and transmembrane domains in a single open reading frame. While the function of these sequences has not been determined, they may prove to be useful for developing a model to study the function of P-glycoproteins.